PROVERBS IN FEATURE INTERVIEWS: A COGNITIVE-DISCURSIVE STUDY OF OPRAH WINFREY’S INTERVIEWS - Konstantinova, Anna (Proverbium - Yearbook, 2011)
In this article Anglo-American proverbs are studied within the framework of the cognitive-discursive approach in linguistics. Oprah Winfrey’s print feature interviews were selected as the material for analysis. First, we single out the characteristics of O. Winfrey’s interview discourse relevant for our research. Next, we look at the functions proverbs fulfill on the structural level of the interview discourse. Last, we analyze the way proverbs (and proverbial expressions) function on the thematic/content level.